Clinical side effects after oral administration of palm oil and Alchornea cordifolia decoction in a child - Paulo Muntu Bunga; Jephté Bambi Nzita; Gerry Mubungu; Sophie Nyembo Mangaza; Nono Joelle Seudjip; Michel Ntetani Aloni (PAGEPress Publications, 2018)
Alchornea cordifolia is known to be a plant with a variety of medicinal properties and is quoted by many traditional healers to treat a variety of medicinal problems in the Democratic Republic of Congo. However, very little is known about its potential toxicity. We report the case of a 9-year-old boy referred for assessment of suspected bronchial troubles without a history of atopic disease or drug allergy who developed dyspnea, dysphagia, asthenia and lingual ulcers within 30 minutes after nasal and oral administration of decoction of palm oil associated with A. cordifolia leaves in water. In the present report, adverse effects of A. cordifolia therapy may be related to the mixtures of active compounds that they contain and can cause the symptoms observed in our patient. These findings call for caution in the use of A. cordifolia especially in children.